Da efemeridade à re-existência - Valentim, Anamélia Fontana (2018)
This study proposes to think of fashion by going beyond the notion of ephemerality, seeking meaning in survival as a form of re-existence. In order to problematize the system that builds fashion, it was necessary to destabilize concepts inherent in it, such as origin, newness, linearity, temporality, as well as its historical construction. The research sought to detect lines of flight present within the system itself and brought them closer to the concept of rhizome. Thinking of fashion as an image and later as a rhizome broadened our perspective at the political possibilities that happen in the assemblages that fashion promotes. With this exercise we challenge the unsustainability of fashion as a promoter of change, especially when based on its material aspect. The re-existence in this study allows for a possibility to look at fashion that understands that the empty changes provoked by ephemerality in fashion remain by excess, and the necessary changes are those that survive the test of time, whether as image, form, style or shared meaning.